ENGINEERING AESTHETICS AND AESTHETICS ERGONOMICS EVALUATION TOOLS IN PRODUCT DESIGN AND DEVELOPMENT - Sivakumar, Dhar Malingam; Sivarao, Subramonian; Tan, Chee Fai (2006)
In the 21st century as the society and market become more sophisticated and the manufacturing technologies become further developed. To compete and succeed in the marketplace, manufactures will have to look beyond reliability and physical quality and pay more and more attention to the aesthetics and subjective quality of their products. While aesthetics and appearance have always played a role in the product and system design, this role will dramatically increase. In the more established technology sectors, functional aspect is a basic in any product and a must to enter the market place. In the verge of competition, cost and aesthetics aspects are among the main factors that often separate the winners and losers.